1985
DOI: 10.1007/bf02310007
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification and partial characterization of an endopolygalacturonase fromCryptococcus albidus var.albidus

Abstract: Cryptococcus albidus var. albidus produced an extracellular endo-polygalacturonase (poly (1,4-alpha-D-galacturonide) glycanohydrolase EC 3.2.1.15) when grown in a synthetic medium containing one of a variety of pectic substances or galacturonic acid. The highest level of enzyme activity (15.5 VU X ml-1) was obtained after 72 h of growth on 1.0% low-methoxyl pectin. The enzyme, purified by gel filtration (Sephadex G-100) after repeated ammonium sulphate precipitation and dialysis, showed only one band by polyac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 20 publications
4
35
0
Order By: Relevance
“…albidus strain IMAT-4735. 11) In our preliminary results, the type strain of C. albidus IFO 0378T did not produce a detectable level of PGase (data not shown). Therefore, production of PGase might be a unique property of strain IMAT-4735.…”
Section: )mentioning
confidence: 75%
“…albidus strain IMAT-4735. 11) In our preliminary results, the type strain of C. albidus IFO 0378T did not produce a detectable level of PGase (data not shown). Therefore, production of PGase might be a unique property of strain IMAT-4735.…”
Section: )mentioning
confidence: 75%
“…The presence of this kind of enzymes has been reported in some yeast species including Saccharomyces fragilis [5], Kluyveromyces marxianus [6], and Cryptococcus albidus [7]. Although Saccharomyces cerevisiae is an important yeast in the food industry, PG production has only recently been described and characterized in a few strains [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Pectinases have also been reported in Kluyveromyces marxianus , K. fragilis (Schwan et al, 1997 ), K. lactis (Sakai et al, 1984 ) and Geotrichum lactis (Murad and Foda, 1992 ), which produces an endo-PG assumed to be important in the breakdown of the pectinaceous layer surrounding coffee and cocoa beans during processing (Pardo et al, 1991 ). It has been found that production of pectolytic enzymes in yeasts is a constitutive property and does not require pectin and polygalacturonic acid to induce the synthesis of these enzymes, whereas certain species like C. albidus (Federici, 1985 ), G. lactis (Pardo et al, 1991 ) and K. fragilis (Garcia-Garibay et al, 1987 ) are inducible. It has been reported in K. marxianus and S. cerevisiae that presence of inducer (pectin) does not influence the production of pectolytic enzymes (Schwan and Rose, 1994 ;Blanco et al, 1994 ).…”
Section: Production Of Yeast Pectinasesmentioning
confidence: 94%
“…It has also been reported in literature that the production of pectic enzymes from yeasts are subjected to catabolite repression. It has been reported in S. cerevisiae (Blanco et al, 1994 ;Blanco et al, 1997 ) and C. albidus (Federici, 1985 ) that production of pectinase enzymes was repressed by presence of carbon source. The production of PG was found to be repressed in K. marxianus when the glucose concentration in the medium was around 10% (w/v) (Schwan and Rose, 1994 ).…”
Section: Production Of Yeast Pectinasesmentioning
confidence: 98%